The carolactam strategy is ineffective: synthesis and biological evaluation of carolactam. Issue 40 (3rd October 2017) - Ammermann, Jonas; Schmidt, Thomas; Donner, Jannik; Reck, Michael; Dalton, Marly; Stumpp, Nico; Stiesch, Meike; Wagner-Döbler, Irene; Kirschning, Andreas
Abstract : The lactam analogue of carolacton was prepared which has lost biofilm inhibitory activity towards Streptococcus mutans . Abstract : Carolacton, a secondary metabolite isolated from the extracts of Sorangium cellulosum, causes membrane damage and cell death in biofilms of the caries- and endocarditis-associated bacterium Streptococcus mutans and Streptococcus pneumoniae . It is known that macrolactam derivatives can show improved pharmacological properties compared to the corresponding macrolactons (lactam strategy). Therefore, we here report the total synthesis and biological activity of the lactam derivative of carolacton ("carolactam"). Carolactam was inactive against planktonic cultures of S. pneumoniae and caused damage of S. mutans biofilms at high concentrations only (above 10 μM). Preliminary modeling studies indicate substantial conformational differences between carolacton and carolactam.